MEASUREMENT-TO-MEASUREMENT BLOOD PRESSURE VARIABILITY IS RELATED TO COGNITIVE PERFORMANCE: THE MAINE-SYRACUSE STUDY - Crichton, Georgina E. (2014)
The objective was to investigate the association between variability in blood pressure and cognitive function for sitting, standing and reclining blood pressure values, and variability derived from all 15 measures. In previous studies only sitting blood pressure values have been examined, and only a few cognitive measures have been employed. A secondary objective was to examine associations between blood pressure variability and cognitive performance in hypertensive individuals stratified by treatment success. Cross-sectional analyses were performed on 972 participants of the Maine Syracuse Study for whom 15 serial blood pressure clinic measures (5 sitting, 5 recumbant and 5 standing) were obtained, prior to testing of cognitive performance. Using all 15 measures, higher variability in systolic and diastolic blood pressure was associated with poorer performance on multiple measures of cognitive performance, independent of demographic factors, cardiovascular risk factors, and pulse pressure. When sitting, reclining and standing systolic blood pressure values were compared, only variability in standing blood pressure was related to measures of cognitive performance. However, for diastolic blood pressure, variability in all three positions was related to cognitive performance. Mean blood pressure values were weaker predictors of cognition. Furthermore, higher overall variability in both systolic and diastolic blood pressure was associated with poorer cognitive performance in unsuccessfully treated hypertensive individuals (with blood pressure ≥140/90 mmHg), but these associations were not evident in those with controlled hypertension.